A importância da comunicação para a cooperação e coordenação das ações da equipe de emergência do SAMU-Natal - Santana, Nathaly Silva de (2020)
This work aims to analyze how communications between members of SAMU emergency teams, and between them and other operators, interfere in cooperation actions between them and in their coordination and impact on the efficiency of this service provided to the population of city of Natal-RN, Brazil. For this, the participative and situated method of Ergonomic Analysis of Work-EAW was adopted. This sought to identify factors that influence the communication, cooperation, coordination and activities of SAMU teams and to propose indications of improvement in work situations, in order to favor the improvement of the quality of communication, cooperation and the coordination of actions. The main problems observed, related to the work of SAMU teams, which interfere with the work of the mobile service team, were the following: a) failures in radio transmissions between the regulation center and the assistance teams (mobile service); b) the occurrence of long waits in the telephone contacts made by the Medical Regulation Assistant Assistants - TARMs with the health units of the patient's final destination; c) delay of the patient's final destination unit to receive the SAMU mobile care team and, consequently, to receive the patient, increasing the time to start the continuity of the patient's hospital care; d) failures in closed loop communication practices. In the activities of the teams, some aspects that positively contribute to the efficiency of the activity were also identified, such as: a) the existence of cooperation between the members of the mobile service team, between the members of the Regulation Central team and between the teams ; b) coexistence between members of the same mobile service team, increasing experience, the efficiency of communication and cooperation and the synergy developed by the mobile service team over time; c) communication as a fundamental factor for the coordination of mobile service teams, through the radios and telephones of the Regulation Center. The main measures recommended to improve communication between teams and, therefore, the coordination of actions, cooperation between them and patient safety, are as follows: a) offer team communication training for members of the mobile care team, between them and the members of the Central Regulation team, between the members of the Central Regulation team and the health units of destination of the patients, highlighting their importance for the efficiency of the service and the safety of the patient; and b) encourage the use of closed loop communication practice, as it reduces the risk of failure to understand the statements and actions; c) to establish fixed mobile care teams as a strategy to improve cooperation and synergy between team members and health care, but, periodically, make changes in the formation of teams so that these new formations also acquire the ability to cooperate and the minimum necessary synergy; d) expand the distribution of radio antennas in the city, to improve the signal and reduce transmission failures; e) hold quarterly meetings with the teams of the Regulation and Mobile Service Center, in which they learn about the service's response time and seek to know the causal factors that lead to this indicator, so that strategies can be established to minimize rational of this time.